Studies of total harmful gas flows on the ground surface from spontaneous mine fires in Kuzbass; Eurasian Mining; № 2 - Lugovtsova N. Yu. Nataliya Yurievna; Timofeeva S. S. Svetlana Semenovna; Demenkova L. G. Larisa Gennadievna; Filonov A. V. Alexandr Vladimirovich (2017, 2017)
Title screen